www. virtualtrials. com – a wide, new database concerning brain tumors - Mackiewicz, Małgorzata; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 1999)
The internet site www. virtualtrials. com is a professionally designed database for physicians and patients as well. It contains a broad spectrum of information concerning brain tumors. Despite the fact that this site has been created recently, it may shortly become a very valuable source of information in this field of oncology, due to the wide database and continuous updating.